PENGEMBANGAN KELOMPOK USAHA MANDIRI MASYARAKAT (KUMM) MENUJU KOPERASI SYARIAH - Nurul Huda; Nazwirman Nazwirman (Universitas Islam kalimantan MAB, 2018)
Community Service that will be done is part of Tridharma Higher Education activities as well as efforts to contribute to develop micro business. The Object of Community Service is some Majelis Taklim Independent Community Business Group (KUMM) is located in the district of Tanjung Priok.Implementation of the activities of the participants assessed the level of satisfaction both from the dimensions of the speaker, training materials, atmosphere, and means. Knowledge skills from before the activities are carried out as evidenced by the pre and post test. The objective is to establish Sharia Cooperative as an instrument of business development of KUMM by using training and mentoring approach.